The Impact of the National Heart Foundation's Warning Signs Campaign on Health-Seeking Behaviour in Acute Coronary Syndrome Patients - Bray, Janet; Nehme, Ziad; Finn, Judith; Smith, Karen; Lim, Michael; Bladin, Christopher; Stub, Dion; Cameron, Peter (LIPPINCOTT WILLIAMS & WILKINS, 2018)
Introduction: Improving acute coronary syndrome (ACS) patient’s recognition and response to symptoms is key to reducing prehospital deaths. Between 2009 and 2013, the Heart Foundation of Australia ran paid mass media campaigns to improve Australians awareness of ACS symptoms and to call emergency medical services (EMS) if symptoms were experienced. This study aimed to examine the impact of this campaign on EMS use and referrals from general practitioners (GPs) in emergency department (ED) presentations in Victoria (Australia). Methods: The Department of Health and Human Services provided data from 39 public EDs contributing data to the Victorian Emergency Minimum Dataset between 2003 and 2015. We included admissions diagnosed with ACS in the dataset, and excluded presentations from aged-care facilities and inter-hospital transfers. We used logistic regression to examine the association between the campaign period and 1) EMS use and 2) patients referred to ED by GPs. Models were adjusted for the increasing population size and known predictors available in the dataset (age, sex, preferred language of English, resident of major city and presentation in winter). Results: Over the study period, there were 127,176 eligible ACS presentations (66,555 acute myocardial infarctions): 64% were male, 58% were aged over 64 years, 70% were a resident of a major city and in 90% English was their preferred language. Overall, 62% of ACS patients arrived by EMS and 8% presented via GPs. After adjusting for confounders, a significant increase in EMS use was seen during the period of campaign activity in ACS patients: adjusted odds ratio (AOR) =1.05 (95% CI:1.02-1.09, p=0.003). While, ACS ED presentations via GPs were seen to decrease (AOR=0.89, 95%CI:0.84-0.95, p<0.001). Patients presenting via their GP were less likely to arrive by EMS (42% vs. 64%, p<0.001). Conclusion: The Warning Signs Campaign was associated with an increase in EMS use and a decrease in ED presentations via GPs in ACS patients. Our study supports the use of public campaigns to change health seeking-behaviour for ACS. Future interventions need to focus on improving EMS use in patients presenting to GPs.